Stigmaeus exilis, a new fusiform species of Stigmaeus Koch (Acariformes: Stigmaeidae) from Sansa, Turkey - Salih Doğan; Sibel Doğan (Persian Journal of Acarology)
A new species of the genus Stigmaeus (Stigmaeidae), S. exilis sp. nov., is described based on the adult females collected from soil in a dead walnut tree hollow from Sansa Gorge, Turkey. Illustrations and phase contrast microscopic images of the new species are also given here. This species can be distinguished by having thin and slender body, anterior margin of prodorsum microtuberculate, posterior margin of propodosomal shield indenting forward by striae, apodemal marking present, eyes and postocular bodies absent, median zonal shield entire, suranal shield entire and bearing three pairs of setae, and femur II with four setae.